Off-label intravenous thrombolysis for early recurrent brain embolism associated with aortic arch thrombus - Koutroulou, Ioanna (Neurol Res Pract, 2021)
Safety data of intravenous thrombolysis (IVT) in presence of aortic arch thrombus is scant. Furthermore, IVT is debatable in patients with prior recent stroke. We present a 51-year-old woman with recurrent major infarction 5 days after a minor left MCA territory stroke. She had a floating aortic arch thrombus and she was treated safely and effectively with off-label IVT. Patients with small infarct volumes and mild/no residual neurological deficits after an initial stroke might be considered for IVT in case of early recurrence. IVT may be reasonable in a context of acute severely disabling stroke associated with aortic arch thrombus.